Problematika Pengaturan Mengenai Bentuk Badan Usaha Jasa Penunjang Tenaga Listrik Di Indonesia - Putra, Vioxcy Ananta; Sulistyowati, Eny; Masnun, Muh Ali (Jurnal Hukum & Pembangunan, 2020)
Legal development electricity growing rapidly as evidenced by the amount of law and regulations produced by both legislative and executive that govern all aspects about electricity that resulting in regulatory inflation in electricity law. The consequences of regulatory inflation in electricity law is the potential for legal unsynchronization between law and regulations in electricity sector. One of the potential for legal unsynchronization in the electricity sector is the regulation regarding the scope and form of business entities supporting electricity power in Law of the Republic of Indonesia Number 30 of 2009 on Electricity, Regulation of the Goverment of the Republic of Indonesia Number 107 of 2015 on Electricity Support Services Business, Regulation of the Minister of Energy and Mineral Resources Number 38 of 2018 on Procedures for Electricity Accreditation and Certification, and Regulation of the Minister of Energy and Mineral Resources Number 12 of 2016 on The Amendment to the Regulation of the Minister of Energy and Mineral Resources Number 35 of 2013 on Procedure for Electricity Business Licensing. Tis research use a type of normative legal research to find the rule of law, legal principles, and relevant legal doctrine and conduct a study of legal concept.